KEDUDUKAN DAN KEKUATAN HUKUM SURAT EDARAN MAHKAMAH AGUNG TENTANG LARANGAN PAILIT KEPADA PENGEMBANG (DEVELOPER) - Yitawati, Krista; Sarjiyati, Sarjiyati (MAKSIGAMA, 2025)
ABSTRACT This study explores and analyses the position and legal force of the Supreme Court Circular Letter (SEMA) issued by the Supreme Court, which regulates the prohibition of bankruptcy or suspension of debt payment obligations (PKPU) experienced by developers. The approach applied in this study is normative legal research. SEMA does not have a position in the hierarchy of laws and regulations and is only a circular issued by the leadership of the Supreme Court in the form of instructions, admonitions, or warnings, and its validity is only binding for judicial institutions under it. However, this legal product should not reduce the freedom of judges in examining and making decisions on a case. The prohibition on filing for bankruptcy and PKPU for developers of apartments and flats hinders the right of creditors or consumers to obtain justice. Meanwhile, bankruptcy and PKPU are tools that can help companies that are facing financial difficulties. Although consumers still have another legal alternative, namely civil suits, to obtain justice, this step is less effective given the large number of housing consumers. This mechanism can legally restructure the company's debt and provide legal certainty for creditors.